Nutrients Content and Biological Test of Vegetable Oil - Ali Khomsan (Media Gizi dan Keluarga, 2000)
The objectives of the research were to analyze saturated and unsaturated fatty acids of vegetable oil; total cholesterol, LDL cholesterol, HDL cholesterol, and triglyceride in blood serum of rat fed by various vegetable oil. Wistar strain rats were grouped into 6 group oil rations i.e. : corn, sorbean, coconut, palm oil 1, palm oil 2, and palm oil 3. Chromatography gas was used to analyze fatty acid content. The result showed that palm oil 1, 2, and 3 contained 47.20%, 43.80%, and 38.80% unsaturated fatty acid. While corn oil, soybean opil, and coconut oil contained 67.30%, 61.64%, and 6.77%. The total cholesterol ranged between 83.99-98.43 mg/100 ml (no difference among groups). The HDL cholesterol of rat with corn oil ration was the lowest. The other groups had HDL cholesterol ranged 28.43-31.90 mg/100 ml. Only corn oil ration showed a statictical difference (p